Pengaruh Robotic Therapy dalam Meningkatkan ROM dan Memperbaiki Tonus Pasien Stroke Iskemik - Pangesti, Adelia; Julianti, Hari Peni; Pudjonarko, Dwi; Rahmawati, Maria Belladonna; Ismail, Rifky (RSUP Dr. Kariadi, 2021)
Background: After stroke occurs, the patients generally have upper extremity hemiparesis. It makes movement restrictions due to decreased elbow active ROM and abnormal upper arm muscle tone, so they need to get rehabilitation therapy. Besides conventional therapy, robotic therapy has now been developed to restore their motor funtions. Objective: To prove that the effect of robotic therapy in increasing elbow active ROM and improving upper arm muscle tone in ischemic stroke patients is better than the effect of conventional rehabilitation exercises. Methods: A quasy-experimental study with two groups pre-test and post-test design was carried out among outpatient ischemic stroke patients in Diponegoro National Hospital and William Booth General Hospital Semarang which was chosen using consecutive sampling.The interventions were by doing exercises using an exoskeleton robotic hand in the robotic group and conventional rehabilitation exercises in the control group. Pre-test and post-test data of robotic group were analyzed using Wilcoxon test, while pre-test dan post-test data of control group were analyzed using Wilcoxon test and paired t-test. Pre-test an post-test data between two groups were analyzed using Mann-Whitney test and unpaired-t test. Results: The robotic group experienced an insignificant increase in ROM (p= 0,593) and significant improvement in muscle tone (p= 0,025). The control group experienced insignificant reduction in ROM (p= 0,980) and insignificant improvement in muscle tone (p= 0,081). Conclusion: There was a significant improvement of upper arm muscle tone in ischemic stroke patients after had exoskeleton robotic hand exercise. Keywords: Stroke, elbow active ROM, muscle tone, exoskeleton robotic